2019
DOI: 10.7717/peerj.7092
|View full text |Cite
|
Sign up to set email alerts
|

Association between VDR gene FokI polymorphism and renal function in patients with IgA nephropathy

Abstract: Background Studies have shown that the occurrence and development of IgA nephropathy (IgAN) are genetically susceptible, but the relationship between vitamin D receptor (VDR) gene polymorphisms and renal function in IgAN patients is unclear. Methods We investigated the relationship between VDR FokI (rs2228570) single nucleotide polymorphism (SNP) and renal function and related clinicopathologic parameters in IgAN patients. Clinical and pathological data of 282 IgAN patients treated at the First Affiliated Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Many previous studies on dyslipidemia have revealed that it is not only a risk factor for the occurrence and development of cardiovascular diseases but aggravates the progression and prognosis of IgAN [10]. Research has shown that the incidence of dyslipidemia in adult IgAN is 45.3-61.1% [9,18,19]. At present, there are few studies on the clinicopathological characteristics and renal outcomes of IgAN complicated with dyslipidemia in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies on dyslipidemia have revealed that it is not only a risk factor for the occurrence and development of cardiovascular diseases but aggravates the progression and prognosis of IgAN [10]. Research has shown that the incidence of dyslipidemia in adult IgAN is 45.3-61.1% [9,18,19]. At present, there are few studies on the clinicopathological characteristics and renal outcomes of IgAN complicated with dyslipidemia in China.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is present in many chronic kidney disease (CKD) patients, and it is also one of the independent risk factors for the progression of kidney disease [8]. Several lines of evidence have suggested that dyslipidemia is related to clinical symptoms, disease progression, and prognosis of the patients with IgAN [9,10], and it is also a risk factor for IgAN to enter ESRD [11]. Nevertheless, few studies involve pathological factors (especially the Oxford classification).…”
Section: Introductionmentioning
confidence: 99%
“…Mo et al reported higher levels of blood urea nitrogen, serum phosphorus, mesangial cellularity/cell proliferation, interstitial fibrosis/tubular atrophy and crescents in VDR rs2228570T allele carriers compared with non-T allele carriers, whereas eGFR and 25-Hydroxyvitamin D3 were lower in T-allele carriers compared with non-T allele carriers among IgAN patients, indicating a role for VDR in the pathogenesis of IgAN [33]. ADM, a vasodilator peptide abundantly expressed in kidneys, shows enrichment with pathways that positively regulate apoptosis.…”
Section: Plos Onementioning
confidence: 99%
“…Genetic causes guide the occurrence and progression of IgAN: Shi et al [ 126 ] demonstrated that IgAN progression in subjects with moderate and high genetic risk was 2.12- and 3.61-fold higher than in those with low genetic risk. In support of this concept, Mo et al [ 127 ] studied the relationship between VDR FokI single nucleotide polymorphism and renal function in IgA patients: the subjects presenting VDR FokI TT genotype had an increased risk of renal dysfunction, demonstrating a potential utility in prediction of the progression of the disease. VDR polymorphisms may aggravate IgAN by inhibiting active vitamin D’s protective role, worsening endothelial cells dysfunction, mesangial cell proliferation, and podocyte and tubulointerstitial damage [ 128 ].…”
Section: Vitamin D In Iga Nephropathymentioning
confidence: 99%